Strategic Planning for Improving Employee Performance Solution Team at Information Technology Company in Jakarta - Astri Ayudia Wibowo; Luki Karunia; Rathoyo Rasdan (PT. Mega Mas Abadi Konsultan, 2025)
This study aims to formulate a comprehensive strategy for improving team performance through structured human resource planning and standardized operational procedures. PT XYZ, a company specializing in data analytics and artificial intelligence, faces performance challenges within its Solution Team due to uneven competency levels and workload distribution. A qualitative research approach was employed, using Focus Group Discussions (FGD) with senior and middle managers as the primary data collection method. The analysis proceeded through three sequential stages: (1) mapping internal human resource elements using the HR Model Canvas, (2) identifying and developing strategic alternatives through the SOAR (Strengths, Opportunities, Aspirations, Results) framework, and (3) evaluating and prioritizing strategies using the Quantitative Strategic Planning Matrix (QSPM). Findings reveal that the “Cross-Training Presales” strategy achieved the highest attractiveness score (4.46) and was established as the top priority. This strategy effectively addresses skill gaps, balances workload distribution, and enhances service quality consistency. The study contributes theoretically by demonstrating the complementary use of HR Model Canvas, SOAR, and QSPM as an integrated framework for strategic performance management. Practically, it provides actionable guidance for PT XYZ and similar technology-based firms to design measurable and standardized work plans that sustain employee and team performance improvement.